Integrated Weed Management in Summer Maize in Mid-Hills of Nepal - Bhattarai, Rajendra Kumar; Chaulagain, Bhimsen; Gaywaly, Pankaj; Karki, Tika Bahadur; Neupane, Reshama; Das, Soni Kumari; Kaduwal, Sangita (Agronomy Journal of Nepal, 2022)
Weed is one of the major problems in maize production. To develop an appropriate weed management practice, a field experiment was carried out during 2017 and 2018 at Khumaltar. Twelve different treatments, Pendimethalin as pre @ 1.0 kg a.i ha-1, Atrazine as pre @ 1 kg a.i ha-1, Metribuzine as pre @ 0.5 kg a.i ha-1, Tembotrione as post @ 0.2 kg a.i ha-1,  Pendimethalin followed by (fb) 1 HW, Atrazine fb 1 HW, Metribuzine fb 1 HW, Tembotrione fb 1 HW,  Atrazine + Metribuzine (early post ) as tank mixed, Straw mulch, Weed free (2 HW) and Weedy check (control) were evaluated in Randomized Complete Block Design (RCBD) with three replications. The experimental plot size was 12 m2 and maize variety Manakamana -4 was sown on 21 and 26 May in 2017 and 2018 respectively. The  seed rate used was 20 kg ha-1 with row spacing of 60 cm and plant to plant 20 cm. Fertilizers dose of 120:60:40 kg N:P2O5:K2O kg ha-1 was applied. Data on crop growth, weed and yields were recorded and analyzed. Weed count and biomass were recorded from a meter square quadrat and yield data taken from net plot of 5.4 m2. Results showed that plant height with straw mulch was maximum of 294 cm. Weed density was significantly influenced by different weed management treatments. Metribuzine post fb 1 HW recorded the less weeds (52.8) and highest (258.5) in weedy check. The lowest weed dry biomass was recorded in Metribuzine post fb 1 HW (9.3 g m-2). The highest grain yield (7.6 Mt ha-1) was found in Metribuzine @ 0.5 kg a.i ha-1 as post emergence. The increased in grain yield due to the application of Metribuzine @ 0.5 kg a.i ha-1 as post emergence was 32.5% over the weedy check. Similarly, the highest weed control efficiency (77.1%) and the highest BC ratio (2.46) was also recorded in Metribuzine @ 0.5 kg a.i ha-1 as post emergence.